Microblogging Design for Education in Visual Message - Vina Mahdalena; Lusia Handayani; Uljanatunnisa Uljanatunnisa (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2023)
The highest increase in social media users reached 34.2% in 2017. Meanwhile, Whatsapp is the most widely used social media in Indonesia. The percentage record at 88.7%. After that, there are Instagram and Facebook, with percentages of 84.8% and 81.3%. Microblogging on Instagram feature is usually for marketing and promotion, but content creators use it as a medium of education in today's society. This medium stimulates teachers to take advantage of Microblog for learning media. This study aimed to test the feasibility of microblogging design concerning the development of learning media in designing visual messages on social media and analyzing microblogs used for education. These research methods are development design and qualitative research. Researchers use experts to assess the microblogging design and collect data by interviewing experts regarding microblogging as an educational medium. The study's result in the form of a Microblog design considers that several categories still need to reach the media feasibility test. Some categories that still need to be feasible are form (element), line, and space. Revision is needed because it will affect the effectiveness of Microblog as a learning medium for students. Microblog for collaborative learning is needed for andragogy learning methods needed by adults. Another unique finding is educational microblogs which present picture stories and are more popular than images. The researcher designed Microblog by paying attention to visual communication to provide education.